Benign regulation of the gut microbiota: The possible mechanism through which the beneficial effects of manual acupuncture on cognitive ability and intestinal mucosal barrier function occur in APP/PS1 mice - Hao, Xin; Ding, Ning; Zhang, Yue; Yang, Yichen; Zhao, Yali; Zhao, Jun; Li, Yiran; Li, Zhigang (Frontiers in Neuroscience, 2022)
Background: Gut microbiota dysbiosis and intestinal barrier injury play vital roles in Alzheimer’s disease (AD) onset and development. Our previous studies have demonstrated that manual acupuncture (MA) could improve the cognitive abilities of APP/PS1 mice. However, the effect of MA on the intestinal mucosal barrier and the gut microbiota mechanism through which this effect occurs remain to be clarified. Methods: In the APP/PS1 manual acupuncture (Am) group , MA was applied at Baihui (GV20), Yintang (GV29) and Zusanli (ST36). Mice in the APP/PS1 antibiotic + manual acupuncture (Aa) group were treated with an antibiotic mixture and MA at the same time. Probiotics were delivered to the APP/PS1 probiotics (Ap) group. Alterations in spatial learning and memory, the gut microbiota, intestinal barrier function and the expression of GFAP, lipopolysaccharide (LPS) and TNF-α were evaluated in each group. Results: Compared with the C57BL/6 control (Cc) group, cognitive ability was significantly decreased, gut microbiota structure was obviously disrupted, intestinal barrier integrity was drastically impaired, and the intestinal inflammatory response was enhanced in the APP/PS1 control (Ac) group (P <0.01). These changes were reversed by MA and probiotics (P < 0.01 or P < 0.05), whereas antibiotics inhibited the benign regulation by MA (P < 0.01 or P < 0.05). Conclusion: MA can benignly modulate gut microbiota dysbiosis, significantly reduce intestinal inflammation and effectively alleviate the destruction of the intestinal mucosal barrier in APP/PS1 mice, and the effects are comparable to those of probiotics. The gut microbiota may play an important role in the improvement of cognitive function and intestinal barrier function by MA.